THE ROLE OF THE OIL INDUSTRY IN THE FERGANA REGION IN THE HISTORY OF UZBEKISTAN IN 1925-1940 - Khusnida Ergasheva (International Journal Of History And Political Sciences, 2023)
The article discusses the importance of hydrocarbon fuel, which stimulated the development of the economy of Uzbekistan and the rise of the entire industry, by studying the history of the oil industry in the Fergana Valley in 1925-1940. After the national territorial demarcation, the extraction of oil from oil wells and the processes of its processing were studied in connection with all sectors of the national economy during the five-year period planned on the basis of the procedures established by the Soviet government. The article is devoted to the history of the oil industry in the Fergana Valley in 1925-1940, based on archival documents in the funds of the National State Archive of Uzbekistan, scientific research of foreign and local researchers, and includes conclusions on the topic.